The revolution generation [videorecording (DVD)] - Tickell, Joshua; Goorjian, Michael A., 1971-; Rodriguez, Michelle; Rodriguez, Michelle (Greenwich Entertainment, 2021)
It is an exploration of the world-changing activism and potential of the largest youth generation in history. The film shows examples of young leaders working to revolutionize systems that have failed their generation. It paints a powerful and hopeful picture of how today's youth can solve global political and environmental crises